Elucidating the Effect of Planar Graphitic Layers and Cylindrical Pores on the Storage and Diffusion of Li, Na, and K in Carbon Materials. (28th February 2020) - Olsson, Emilia; Cottom, Jonathon; Au, Heather; Guo, Zhenyu; Jensen, Anders C. S.; Alptekin, Hande; Drew, Alan J.; Titirici, Maria‐Magdalena; Cai, Qiong
Abstract: Hard carbons are among the most promising materials for alkali‐ion metal anodes. These materials have a highly complex structure and understanding the metal storage and migration within these structures is of utmost importance for the development of next‐generation battery technologies. The effect of different carbon structural motifs on Li, Na, and K storage and diffusion are probed using density functional theory based on experimental characterizations of hard carbon samples. Two carbon structural models—the planar graphitic layer model and the cylindrical pore model—are constructed guided by small‐angle X‐ray scattering and transmission electron microscopy characterization. The planar graphitic layers with interlayer distance <6.5 Å are beneficial for metal storage, but do not have significant contribution to rapid metal diffusion. Fast diffusion is shown to take place in planar graphitic layers with interlayer distance >6.5 Å, when the graphitic layer separation becomes so wide that there is negligible interaction between the two graphitic layers. The cylindrical pore model, reflecting the curved morphology, does not increase metal storage, but significantly lowers the metal migration barriers. Hence, the curved carbon morphologies are shown to have great importance for battery cycling. These findings provide an atomic‐scale picture of the metal storage and diffusion in these materials. Abstract : The local diffusion and storage of Li, Na, and K in hard carbon are probed through density functional theory calculations based on small‐angle X‐ray scattering and transmission electron microscopy structural characterization. Curved morphologies and wide planar pores are shown to provide fast metal diffusion, whereas graphitic stacks offer good storage capacity, highlighting that both features are important for efficient anode performance.